2016
DOI: 10.1177/1464419316653002
|View full text |Cite
|
Sign up to set email alerts
|

New approach for the simulation of chain drive dynamics with consideration of the elastic environment

Abstract: In the development and layout of timing chain drives for internal combustion engines, multi-body simulation is used to evaluate the chain drive in terms of both the acoustic and the dynamic behaviour. Owing to the complex structure of chain drives and surrounding components, the system cannot be described by analytical equations. The elastic behaviour of the single components can influence the dynamic and acoustic behaviour of the chain drive system and the timing system. This paper describes a new methodology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Grinschgl et al 25 found the impact velocity and forces at the bearing of the sprocket by creating a three-dimensional finite element model. The chain bed is considered as a rigid body, while the rest of the sprocket is modeled as a deformable body.…”
Section: Introductionmentioning
confidence: 99%
“…Grinschgl et al 25 found the impact velocity and forces at the bearing of the sprocket by creating a three-dimensional finite element model. The chain bed is considered as a rigid body, while the rest of the sprocket is modeled as a deformable body.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 The effect of the polygonal action is to produce a periodic variation in the velocity ratio and a large dynamic load in the chain, 12 thus reducing the chain’s fatigue life and causing noise. 13,14 This undesirable effect motivates researchers to investigate the dynamic behaviour of chain drives.…”
Section: Introductionmentioning
confidence: 99%
“…The simulation results showed that the composite sliding mode controller of the permanent magnet direct drive system can realize the smooth start of scraper conveyor. Grinschgl et al [18] proposed a chain drive modeling strategy combined with multibody simulation and finite element method. They also compared the simulation and experiment of a simple doublechain drive.…”
Section: Introductionmentioning
confidence: 99%